The Influence of Exports and Imports on Indonesia's Economic Growth - Nur Sakinah; Novita Kaban; Hernita Siagian; Rahel Hutahaean; Ginting, Renata Olivia; Desry Tarigan (Outline Publisher, 2024)
The aim of this research is to analyze the influence of exports and imports on economic growth in Indonesia. This research uses secondary data obtained from the Central Statistics Agency for 2012-2023. This research uses multiple linear regression analysis methods and uses several classical assumption tests. To process the data, several tests are used, namely the Statistical Test and the Classical Assumption Test. Data is processed using the Eviews application. From the results of this research, it is known that exports do not have a significant effect on economic growth in Indonesia. Imports also do not have a significant effect on growth in Indonesia.